Decarboxylative dipropargylation of primary amines with propiolic acids and formaldehyde via metal-free coupling. Issue 18 (6th May 2015) - Jia, Huihui; Feng, Huangdi; Sun, Zhihua
Abstract: A metal-free decarboxylative coupling reaction, which produced important and useful dipropargylic amines, was developed under mild conditions. This novel methodology showed a broad range of functional-group compatibility for primary amines and propiolic acids, and gave the corresponding products in up to 97% yields. Graphical abstract: